CONSTRUCTION OF CONCEPTION OF DISABILITY IN LAWS AND REGULATIONS OF LATVIA - Baikovska, Baiba (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Title of article research is “Conception of Disability in Laws and Regulations of Latvia”. Wherewith this research is carried out in communication and disability studies disciplines. This topic for research was chosen because the conception of disability in regulations and laws is impacting overall legislation related to persons with disabilities and thus directly impacting their lives. And Disability law of Latvia is one of the main laws which is directing regulations related to dividing persons with disabilities in groups, receiving of assistant and guide services and similar issues. As basic method for the research of this article was chosen to be critical discourse analysis which according to Norman Fairclough is providing tools to research text, discursive practice related to this text and sociopolitical context. Articles and amendments of Disability law of Latvia has been researched according to theoretical models of disability described, also process related to creation of the law and passage of it and sociopolitical context from which the main part is in 2010 ratified United Nations (UN) Convention for the rights of persons with disabilities which should impact the legislation of Latvia. By doing research the main conclusion made was that in Disability law of Latvia persons with disabilities are seen more from the point view of medical model of disability but in its amendments from the point of view of “gap” model. It can be explained with the ratification of UN Convention for the rights of persons with disabilities and with being in European Union (EU), willingness to bring principles of welfare state in Latvia.